Numerical study of residual stress fields after double-sided symmetric laser shock peening of blade edge (Fracture and Structural Integrity, 2025)
This paper deals with numerical modelling of the residual stress field formed after laser shock peening of a thin blade edge from TC4. It is shown that the application of double-sided symmetric laser shock peening is an effective way of treatment, as it allows to reduce deformation and geometrical changes caused by laser shock peening in comparison with treatment from one side. The results of numerical modelling obtained by varying the machining parameters (power density, spot shape, number of passes, % overlapping) were used to form a database for further training of the neural network. It is shown which machining parameters lead to compressive residual stresses over the entire thickness of the edge, and which ones induce tensile stresses on the surface.
Keywords: Laser shock peening; Numerical modeling; Titanium alloy; Residual stress